Rekayasa Kualitas Bunyi Sound System Menggunakan Desain Eksperimen Faktorial - J. M. Tupan (Industrial Engineering Study Program, Pattimura University, 2010)
Quality is important thing in world industry competition. Availability sound system equipment competitive and produced sound quality is a need to get more customer. This research aim to know noise level and sound distortion, to know cause factors influence and results compared both design experiment results and existing condition results ( V model ). Design experiment factorial 34 method with five replications used to know influence and equalizer setting model, sum of mic, distance of mic and sum of speaker factors interaction with response variable feedback frequency ( Hz ) and sounds feedback pressure (dB) with quality characteristic smaller the better ( SBT ). Result analysis show is quality sounds ( feedback frequency and sound pressure ) was produced from design experiment factorial better than experiment with V model ( general used ). Design Experiment factorial 34 with random model equalizer setting versus sum of speaker 10 combination was produced lower feedback frequency is 170 Hz. It with random model equalizer setting versus sum of mic 3 was produced lower sound pressure is 56.1737 dB.